Pengaruh Latihan Split terhadap Smash Kedeng Atlet Sepak Takraw Kecamatan Pringgabaya - Tamim, Muhammad Husni; Sugiantoro, Arung (TSAQOFAH, 2023)
The Effect of Split Training on the Kedeng Smash of Sepak Takraw Athletes, Pringgabaya District.Sepak takraw is a traditional sport originating from countries in Southeast Asia. This player has been around since the 15th century. Over time, this game began to develop and began to be competed in international tournaments. This research is a cause-and-effect research (experiment) using a One Group Pretest-Posttest Design, namely a group that is given treatment, but before treatment, a pretest is first carried out and then given treatment. After that, another final test (posttest) was carried out. The object of this research was sepak takraw athletes in Pringgabaya District with a population of 8 people and the sample used was 8 people. The data collection technique is using the kedeng smash ability test. The data analysis technique in the research uses descriptive and inferential statistical analysis. Based on data analysis, it was found that the average pre- and post-test kedeng smash ability was 5.25 and 7.5. From hypothesis testing using the independent sample t-test. In the statistical analysis of athletes' kedeng smash abilities through split training, the calculated T value > T table (6.081 > 1.894) was obtained. From these data it can be concluded that the use of split training has an effect on the kedeng smash ability of sepak takraw athletes in Pringgabaya district.